On the Accuracy of Normalcy Approximation in Stochastic C-V-P Analysis: A Comment. - Kottas, John F.; Lau, Hon-Shiang (The Accounting Review, 1978)
The often substantial amount of uncertainty associated with unit volume, unit variable cost, fixed cost, or even unit price in cost-volume-profit (CVP) analysis has made apparent the need for an easy-to-use and accurate means of making probabilistic statements about profit. Over the last dozen years, three main approaches to stochastic CVP analysis have evolved. They are Chebyshev-type inequalities approach, direct simulation approach and theoretical distribution approach. The study of Ferrara-Hayya-Nachman (FHN) considers an important aspect of the third approach. However, the purpose of this paper is to show that the study of FHN is based on inappropriate statistical methodology and their recommendation is, therefore, invalid. Thus, at the current stage of development, it appears that a practitioner should seriously consider using the direct simulation approach. This approach, is easily implemented on even a small computer and provides reasonable levels of accuracy. On the other hand, the facility of application of the theoretical distribution approach to CVP analysis continues to be attractive.